2018
DOI: 10.1080/08985626.2018.1551792
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating business and family demands within a patriarchal society – the case of women entrepreneurs in the Nepalese context

Abstract: The aim of this paper is to advance our understanding of how women negotiate their business and family demands in a developing country context. The highest cited motivation for women's pursuit of entrepreneurship has been their need to attend to these demands. Yet, empirically we know little about the negotiating actions taken by, and the business satisfaction of women in the context of both livelihood challenges and patriarchal contexts, despite several scholarly calls for contextualized accounts of women's e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 62 publications
8
78
0
Order By: Relevance
“…Family assets carry emotional ties that when invested in the woman entrepreneur's venture, can lead to less cohesiveness and undermine business performance (Hatak et al 2016). It has been found that usually businesses are more successful when the owners do not involve the family in the business (Carter and Rosa 1998;Rey-Marti et al 2015) or when negotiation takes place between the family and business demands (Neneh 2018;Xheneti et al 2019). Thus, Hypothesis 3.…”
Section: Effect Of Family Financial Support On Entrepreneurial Successmentioning
confidence: 99%
“…Family assets carry emotional ties that when invested in the woman entrepreneur's venture, can lead to less cohesiveness and undermine business performance (Hatak et al 2016). It has been found that usually businesses are more successful when the owners do not involve the family in the business (Carter and Rosa 1998;Rey-Marti et al 2015) or when negotiation takes place between the family and business demands (Neneh 2018;Xheneti et al 2019). Thus, Hypothesis 3.…”
Section: Effect Of Family Financial Support On Entrepreneurial Successmentioning
confidence: 99%
“…For instance, firms operating in the food industry need to apply for a license from the Department of Food Technology and Quality Control. Rules regarding bank loans are similarly complex, access to which reflect Nepal's traditional social values in terms of land title and inheritance (Xheneti et al 2019a).…”
Section: Informal Economy In the Context Of Nepalmentioning
confidence: 99%
“…Consequently, their positioning within the informal economy changes dynamically over time, for example by the need to improvise their business status in line with family, gender and other (e.g. caste) expectations (Xheneti et al 2019a). The idea of engagement in entrepreneurial activities in the informal economy as an 'opportunity' incorrectly portrays the nature of women entrepreneurship in developing countries, which is more typically characterized by the need for survival and to support livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…At the other hand, Cambodia, the Philippines, Thailand and Vietnam are marked by a weak patriarchy, which means that there is no or restricted cultural ban at women's involvement in any income-generating activity (Jang and Kim 2018). The weak patriarchy enables women to be flexible and their roles negotiable (Xheneti, et al, 2019). Men and women work together to set up joint ventures that contribute to their diverse portfolio of livelihoods.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%